Thirteen-Velocity Three-Dimensional Multiple-Relaxation-Time Lattice Boltzmann Model for Incompressible Navier-Stokes Equations (Advances in Applied Mathematics and Mechanics, 2025)
This paper presents a three-dimensional thirteen-velocity (D3Q13) multiple-relaxation-time (MRT) lattice Boltzmann (LB) model for incompressible flows. Themodel can eliminate the second kind of compressibility error existing in previousD3Q13 MRT LB models. We simulate the three-dimensional steady Poiseuille flow,unsteady pulsatile flow, and lid-driven cavity flow to verify the validity of the current model. The excellent agreement between the numerical result and the analyticalsolution or the previous numerical result demonstrates the model’s effectiveness.